Synthesis of N-type semiconductor diamonds with sulfur,boron co-doping in FeNiMnCo-C system at high pressure and high temperature - 张贺 李尚升 宿太超 胡美华 马红安 贾晓鹏 李勇 (Chinese physics B, 2017)
A series of diamonds with boron and sulfur co-doping were synthesized in the Fe Ni Mn Co-C system by temperature gradient growth（TGG） under high pressure and high temperature（HPHT）. Because of differences in additives, the resulting diamond crystals were colorless, blue-black, or yellow. Their morphologies were slab, tower, or minaret-like. Analysis of the x-ray photoelectron spectra（XPS） of these diamonds shows the presence of B, S, and N in samples from which N was not eliminated. But only the B dopant was assuredly incorporated in the samples from which N was eliminated. Resistivity and Hall mobility were 8.510 Ω·cm and 760.870 cm^2/V·s, respectively, for a P-type diamond sample from which nitrogen was eliminated. Correspondingly, resistivity and Hall mobility were 4.211×10^5 Ω·cm and 76.300 cmΩ2/V·s for an N-type diamond sample from which nitrogen was not eliminated. Large N-type diamonds of type Ib with B–S doping were acquired.